The Influence of Person Job Fit and Person Organization Fit on Employee Performance in the Mining Company: The Mediating Role of Work Engagement - Rofi'ul Latif, Muhammad Alex; Nasution, Nasution Nasution (Universitas Muhammadiyah Pontianak, 2025)
This study was conducted to determine how work engagement functions as a mediating variable in the relationship between employee performance and job fit and organization fit. This study quantitative research. The study was conducted at PT Titan Wijaya and PT Maritim Sumber Energi. The samples in this study is 110 respondents. SmartPLS was the software utilized in this work, and the partial least square structural equation modeling (SEM-PLS) method was used for data analysis was. The results of this study are person job fit and person organization fit have a positive effect on employee performance, work engagement also has a positive effect on employee performance, then person job fit and person organization fit affect work engagement. And work engagement successfully mediates the relationship between person job fit and person organization fit on employee performance. To determine whether these findings can be applied to a wide range of organizations, research should be extended to other industry sectors. Future research can also look at how Organizational Citizen Behavior (OCB) can help improve employee engagement and performance. By using a mixed methods approach, they can gain a better understanding of how relationships between variables occur in the workplace.